Illegal immigration: policy perspectives and challenges - Casarico, Alessandra; Facchini, Giovanni; Frattini, Tommaso (Oxford Journals, 2015)
The combination of increasing immigration pressures and restrictive policies imperfectly enforced by many destination countries has made illegal immigration widespread. This paper provides an overview of the mechanisms behind the formation of migration policies and how they lead to or they limit the presence of illegal immigrants. We also study how governments deal ex-post with the presence of undocumented foreign workers by introducing immigration amnesties. We review the determinants of their introduction and address their desirability from the point of view of aggregate welfare. As countries in the EU differ substantially in the implementation of both ex-ante and ex-post immigration policies, we emphasize the need for more coordination in the area of migration policy enforcement, both at the border and within each country.